2019
DOI: 10.1021/acs.joc.8b03106
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereo- and Enantioselective Access to syn-α-Amido β-Hydroxy Esters via Ruthenium-Catalyzed Dynamic Kinetic Resolution-Asymmetric Hydrogenation

Abstract: Dynamic kinetic resolution (DKR) of racemic aryl α-amino β-ketoesters via Ru-diphosphine-catalyzed asymmetric hydrogenation was realized at 70 °C under 50 atm of hydrogen, affording syn α-amido β-hydroxy esters in high yields (up to 96%) with high reactivity (TON up to 940) and diastereo- and enantioselectivities (up to 99:1 dr, 98% ee). These hydrogenation products provide valuable chiral synthons in many natural products and pharmaceuticals. Gram-scale DKR asymmetric hydrogenation (DKR-AH) was also performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Asymmetric reduction via dynamic kinetic resolution (DKR) is regarded as a powerful synthetic method to simultaneously set up two adjacent stereogenic centers in a single transformation from racemic substrates. , Recently, we developed an efficient asymmetric synthesis of enantiomeric pure syn -aryl β-hydroxy-α-dibenzylamino esters via a DKR asymmetric transfer hydrogenation (DKR-ATH) in high yields . Excellent diastereoselectivity and enantioselectivity were obtained using an oxo-tethered Ru­(II) catalyst that could be applied to a wide range of substrates.…”
Section: Introductionmentioning
confidence: 64%
“…Asymmetric reduction via dynamic kinetic resolution (DKR) is regarded as a powerful synthetic method to simultaneously set up two adjacent stereogenic centers in a single transformation from racemic substrates. , Recently, we developed an efficient asymmetric synthesis of enantiomeric pure syn -aryl β-hydroxy-α-dibenzylamino esters via a DKR asymmetric transfer hydrogenation (DKR-ATH) in high yields . Excellent diastereoselectivity and enantioselectivity were obtained using an oxo-tethered Ru­(II) catalyst that could be applied to a wide range of substrates.…”
Section: Introductionmentioning
confidence: 64%
“…Zhang and co-workers described the synthesis of syn-amido--hydroxy esters through AH/DKR of the corresponding -amido--keto esters using the preformed complex [RuCl(p-cymene)(S)-SunPhos]Cl obtained from [Ru-Cl 2 (p-cymene)] 2 and (S)-SunPhos [(S)-L6] (Scheme 9). 16 This study revealed the importance of the steric and electronic effects of the substituents on the aryl moiety and that the stereoselectivities were also deeply influenced by the nature of the amino protecting group. The hydrogenation proceeded in 66-96% yields with high reactivity (TON up to 940), 58:42 to >99:1 dr, and 51 to >99% ee.…”
Section: Methodsmentioning
confidence: 88%
“…Successively, the organic phases were combined, washed with a saturated sodium bicarbonate aqueous solution (50 mL), filtered, and concentrated in vacuo . The crude product was purified by flash column chromatography (33% EtOAc in petrol) and triturated with Et 2 O to give the carbonyl derivative S7 as a white solid (2.55 g, 14.7 mmol, 40%). R f : 0.36 (90:10 EtOAc:petrol).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…13 Methyl 2-Acetamido-3-oxobutanoate (S7). According to a procedure, 43 a solution of sodium nitrite (3.30 g, 48.0 mmol) in water (4 mL) was added dropwise to a solution of methyl acetoacetate (4.00 mL, 36.8 mmol) in acetic acid (10 mL). After stirring the solution at room temperature for 2 h, water (25 mL) was added and stirred for further 30 min.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%